Peripheral Computing During Presentations: Perspectives on Costs and Preferences - Iqbal, Shamsi; Grudin, Jonathan; Horvitz, Eric (ACM Conference on Human Factors for Computing Systems (CHI), 2011)
Despite the common use of mobile computing devices to communicate and access information, the effects of peripheral computing tasks on people‟s attention is not well understood. Studies that have identified consequences of multitasking in diverse domains have largely focused on influences on productivity. We have yet to understand perceptions and preferences regarding the use of computing devices for potentially extraneous tasks in settings such as presentations at seminars and colloquia. We explore costs and attitudes about the use of computing devices by people attending presentations. We find that audience members who use devices believe that they are missing content being presented and are concerned about social costs. Other attendees report being less offended by multitasking around them than the device users may realize.